2010
DOI: 10.1007/s10658-010-9704-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pectobacterium species from Iran using biochemical and molecular methods

Abstract: Characteristics of forty strains from macerated potato tubers and water-soaked lesions of some ornamental plants were studied in north parts of Iran. The causal organisms isolated from infected tissues were identified as Pectobacterium spp. based on their physiological and biochemical assays and confirmed by species and subspecies specific PCR and RFLP analysis of 16S-23S intergenic transcribed spacer region. Artificial inoculation of isolates to their related hosts generated the same symptoms on potato and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…Thus, it appears that there was no correlation between the presence or absence of a T3SS in these strains and the ability to cause disease. These observations are consistent with those of other researchers (Ma et al 2007;Kim et al, 2009;Pitman et al 2010;Baghaee-ravari et al 2011). …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Thus, it appears that there was no correlation between the presence or absence of a T3SS in these strains and the ability to cause disease. These observations are consistent with those of other researchers (Ma et al 2007;Kim et al, 2009;Pitman et al 2010;Baghaee-ravari et al 2011). …”
Section: Discussionsupporting
confidence: 94%
“…However, there have been several reports of its occurrence in potatoes (Ma et al, 2007;Pitman et al, 2008;Kim et al, 2009;Baghaee-Ravari et al, 2011). Interestingly, Ma et al (2007) previously identified several P. wasabiae strains lacking a type III secretion system (T3SS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, P. c. ssp. carotovorum strains had been shown to vary in their ability to cause HR in tobacco and the presence of type III secretion system (Yap et al, 2004;Kim et al, 2009;Baghaee-Ravari et al, 2011;Nabhan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%